Quand l’artiste contemporain joue au muséographe - Noémie Drouguet (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article deals with the intervention of contemporary artists in order to create themselves museography of exhibitions. Through the presentation of three study cases in society museums, the author shows what exhibitions language should get out of this artistic work, in both aspects of form and content - humorous, provocative or distant approach - even if the exhibition display could also be inspired by classical museal forms.